2021
DOI: 10.1002/mrm.28669
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐corrected proton density fat fraction estimation using chemical shift‐encoded MRI in phantoms

Abstract: Purpose: Chemical shift-encoded MRI (CSE-MRI) is well-established to quantify proton density fat fraction (PDFF) as a quantitative biomarker of hepatic steatosis. However, temperature is known to bias PDFF estimation in phantom studies. In this study, strategies were developed and evaluated to correct for the effects of temperature on PDFF estimation through simulations, temperature-controlled experiments, and a multi-center, multi-vendor phantom study. Theory and Methods: A technical solution that assumes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Spectroscopic and imaging‐based PDFF methods had similar small temperature sensitivities, indicating that performing a T 1 and T 2 correction to the raw spectroscopy data 23 or a frequency correction to the simulated fat spectrum for the imaging data 13 substantially compensates for variation in the measurement due to temperature‐induced changes in tissue relaxation parameters. Navaratna et al have recently demonstrated a similar reduction of temperature sensitivity for MRI PDFF measurements through improved fat spectrum frequency correction in phantom experiments 39 . We believe that much of the remaining variation in measured PDFF could be due to a partial change of state in the fat; that is, we suggest that some hepatic macrovesicular fat droplets begin to solidify at cold temperatures and become “MR‐invisible” due to the extremely short T 2 values seen in this semi‐solid “frozen droplet” state.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Spectroscopic and imaging‐based PDFF methods had similar small temperature sensitivities, indicating that performing a T 1 and T 2 correction to the raw spectroscopy data 23 or a frequency correction to the simulated fat spectrum for the imaging data 13 substantially compensates for variation in the measurement due to temperature‐induced changes in tissue relaxation parameters. Navaratna et al have recently demonstrated a similar reduction of temperature sensitivity for MRI PDFF measurements through improved fat spectrum frequency correction in phantom experiments 39 . We believe that much of the remaining variation in measured PDFF could be due to a partial change of state in the fat; that is, we suggest that some hepatic macrovesicular fat droplets begin to solidify at cold temperatures and become “MR‐invisible” due to the extremely short T 2 values seen in this semi‐solid “frozen droplet” state.…”
Section: Discussionmentioning
confidence: 87%
“…Navaratna et al have recently demonstrated a similar reduction of temperature sensitivity for MRI PDFF measurements through improved fat spectrum frequency correction in phantom experiments. 39 We believe that much of the remaining variation in measured PDFF could be due to a partial change of state in the fat; that is, we suggest that some hepatic macrovesicular fat droplets begin to solidify at cold temperatures and become "MR-invisible" due to the extremely short T 2 values seen in this semi-solid "frozen droplet" state. This would accord with results from food science literature, where increased solid fat content, measured by increased contribution of an ultrashort T 2 compartment, has been seen at lower temperatures in a wide range of substances from lard to chocolate.…”
Section: Correlation Of Imaging Parameters With Histology and Liver Functionmentioning
confidence: 81%
“…As suggested in the original study, 16 the PDFF biases found across sites could be due to the variability of temperature which might affect PDFF quantification. 49,63 Eventually, Fatty-Riot-GC and IDEAL-CE exhibited more FWswaps and bias compared to custom in vitro experiments.…”
Section: 4mentioning
confidence: 99%
“…For this purpose, phantoms, which are experimental replicas of organs or tissues, represent a practical solution for testing and quality control of MRI-based fat quantification. Homemade fat-water phantoms have been described (60,61), although commercial phantoms (eg, Calimetrix PDFF Phantom) are now available (57,62).…”
Section: Mri Examinationsmentioning
confidence: 99%